Sociodemographic and psychosocial correlates of resilience among older adults living with HIV in the Deep South - Brown, Monique J (J Health Psychol, 2020)
This cross-sectional study assessed the psychosocial and sociodemographic correlates of resilience among older adults living with HIV. Data were obtained from 103 men and 53 women aged 50 years and older in South Carolina. Multivariable linear regression models showed that employment (any) (B: 3.52; 95% confidence interval : 1.04, 5.99), education (B: −3.56; 95% confidence interval: −6.15, −0.98), time since diagnosis (B: 0.18; 95% confidence interval: 0.04, 0.31), and social support (B: 0.27; 95% confidence interval: 0.20, 0.34) were associated with resilience. Interventions tailored for older adults living with HIV to support resilience could facilitate social support, particularly for those who are newly diagnosed, unemployed, and have lower educational attainment.